2007
DOI: 10.1097/fjc.0b013e318032002f
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Effects of the Atrial Selective Antiarrhythmic Compound AVE1231

Abstract: The novel compound AVE1231 was investigated in order to elucidate its potential against atrial fibrillation. In CHO cells, the current generated by hKv1.5 or hKv4.3 + KChIP2.2b channels was blocked with IC50 values of 3.6 microM and 5.9 microM, respectively. In pig left atrial myocytes, a voltage-dependent outward current was blocked with an IC50 of 1.1 microM, mainly by accelerating the time constant of decay. Carbachol-activated IKACh was blocked by AVE1231 with an IC50 of 8.4 microM. Other ionic currents, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 33 publications
2
50
0
Order By: Relevance
“…Inhibition of the "early K + channels" I sus and I to may explain the prolongation of AERP in pigs as reported in the present study and the previously reported prolongation of the action potential in rabbit left atrial tissue . It has been clearly demonstrated that inhibition of the early K + channels potently suppresses AF in a pig and goat model of AF (Blaauw et al 2004;Blaauw et al 2007;Wirth et al 2003;Wirth et al 2007).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Inhibition of the "early K + channels" I sus and I to may explain the prolongation of AERP in pigs as reported in the present study and the previously reported prolongation of the action potential in rabbit left atrial tissue . It has been clearly demonstrated that inhibition of the early K + channels potently suppresses AF in a pig and goat model of AF (Blaauw et al 2004;Blaauw et al 2007;Wirth et al 2003;Wirth et al 2007).…”
Section: Discussionmentioning
confidence: 98%
“…Atrial effective refractory period (AERP) was measured in anesthetized pentobarbital thoracotomized pigs with the S1-S2 method at 400, 300, and 240 ms basic cycle lengths (BCLs) as previously described (Wirth et al 2003(Wirth et al , 2007. Briefly, atrial responses to the pacing procedure were measured in the left atrium using a monophasic action potential (MAP) pacing catheter (combined MAP and stimulation catheter, 7 F; Foehr Medical Instruments GmbH, Seeheim, Germany).…”
Section: Investigation Of Atrial Antiarrhythmic Efficacy In Anesthetimentioning
confidence: 99%
“…Due to our observation that these blockers have a strong preference for TASK-1 channels and as the structures of S20951 and AVE1231 were not yet released by Sanofi-Aventis, we published these compound as TASK-1 blockers using the synonyms A1899 [30] for S20951 [16,17] and A293 [27] for AVE1231 [27]. Both compounds were previously described as being effective in animal models against atrial fibrillation [16,17,37], and AVE1231 (A293) had entered clinical development (phase I trial) against atrial fibrillation.…”
Section: Introductionmentioning
confidence: 94%
“…TASK-1 expression in human and pig hearts, unlike that in rodents, is limited to the atria and promotes action potential recovery (Limberg et al, 2011;Schmidt et al, 2014). TASK-1-inhibiting compounds increase cardiac atrial tissue refractoriness and may prevent and/or treat atrial fibrillation (Wirth et al, 2003(Wirth et al, , 2007Kiper et al, 2015). Other TASK-inhibiting drugs with known cardiac pro-or antiarrhythmic properties include lidocaine, bupivacaine, amiodarone, and carvedilol (Kindler et al, 1999;Gierten et al, 2010;Staudacher et al, 2011).…”
Section: Introductionmentioning
confidence: 99%